AHLs-mediated quorum sensing threshold and its response towards initial adhesion of wastewater biofilms. (15th April 2021) - Wang, Jinfeng; Liu, Qiuju; Dong, Deyuan; Hu, Haidong; Wu, Bing; Ren, Hongqiang
Highlights: Bacterial adhesion biomass was significantly improved by exogenous AHLs. Appropriate AHLs that promote bacterial adhesion were selected. The preferred form of AHL and QS response differed for various biofilms. A potential way to improve the settling property of bulking sludge was proposed. Abstract: Quorum sensing (QS) plays a crucial role during initial biofilm formation, however the QS threshold and the response of biofilm formation towards N -acyl-homoserine lactones (AHLs) remains largely unknown due to the limitation of nondestructive online methods for monitoring bacterial adherence and the complexity of QS system, which limits the application of QS signal reagents in biofilm reactors. In this study, bacterial QS threshold and its response of biofilm formation to AHLs in purely cultured Sphingomonas rubra biofilm as well as in three different wastewater biofilms #1–3 were investigated via real time cell analysis (RTCA). The main perspective was to study the biomass adherence in response to 12 different forms of AHLs at different concentrations. Results showed that bacterial adhesion was significantly improved by exogenous AHLs with the maximum increase of 2.26-, 2.36-, 2.52-, and 2.80- times biomass production in the four respective biofilms. Although the preferred form of AHL differed for various biofilms, the long-chain AHLs (12–14 carbons) resulted in an overall improvement of bacterial adhesion due to their stronger hydrophobicity and hydrolysis resistance. In addition, bacterial QS threshold of AHLs was observed to have a wide range of concentration from 10 ng/L to 10 μg/L. Meanwhile, QS response time to AHLs also showed a significant difference in different biofilms. Biofilm #2 inoculated with bulking sludge had lower QS threshold of 10 ng/L and faster response to most AHLs that is less than 6 h. Thus, considering the improvement of biofilm adhesion by AHLs, 10 ng/L of C12-HSL, 10 ng/L of C12-HSL, and 10 ng/L of C6-HSL were preferentially selected for wastewater biofilms #1–3 respectively. Unexpectedly, adding high-concentration of AHLs detected in sludges did not significantly improved the bacterial adhesion. Infact the addition of these AHLs at low concentrations or even undetected concentrations substantially improved bacterial adhesion, which could be explained by bacterial communities composition. According to the Pearson correlation analysis, 62% of the top 50 most abundant genera in bacterial communities were significantly negatively related to the response time of multiple AHLs, representing their fast QS response. The QS bacteria, Dechloromonas and Nitrospira have fast QS response for C4-HSL and C8-HSL while, Comamonadaceae has fast QS response for 3OC8-HSL, 3OC10-HSL, 3OC12-HSL, and 3OC14-HSL. In contrast, the rest 38% of the top most abundant genera, such as Ferruginibacter, Hyphomicrobium, and Terrimonas quickly responded to only one AHL, showing significant negative relationship with the response time of C6-HSL. Overall, this study provides an effective and convenient means to select appropriate AHL reagents to promote bacterial adhesion in biofilm systems. Moreover, it also suggests that exogenous AHLs may be useful in improving the settling property of bulking sludge. Graphical abstract: Image, graphical abstract